FATAL FLAWS: THE LETHAL IMPACT OF UNLICENSED BEAUTY TREATMENTS - Гасенко, Кристина (SWorldJournal, 2024)
The article examines the fatal consequences of unlicensed cosmetic procedures conducted without proper medical oversight and licensing. The study aims to analyze the impact of these illegal services on the health and lives of consumers and to identify eff